2017
DOI: 10.1080/01635581.2018.1397708
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Induces Mitochondrial Apoptosis and Inhibits Epithelial-Mesenchymal Transition in Oral Squamous Cell Carcinoma Cells

Abstract: OSCC is the most common malignant cancer of the head and neck. EMT is an essential cellular process critical to the morphogenesis and homeostasis of solid tissues. It is also involved in the initial stage of cancer metastasis and invasion in which cells lose epithelial characteristics. While cancer therapy protocols such as surgery, radiation, and chemotherapy are effective and useful, the drug tolerance and toxicity of OSCC patients remain a problem. Resveratrol is mainly produced in red grape skin and exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 52 publications
1
47
0
7
Order By: Relevance
“… 20 Research by Kim et al showed that res-veratrol induced mitochondrial apoptosis and inhibited cell invasion and migration by inhibiting epithelial–mesenchymal transition in oral squamous cell carcinoma cells. 21 Resvera-trol was also reported to decrease cell viability and proliferation while induced apoptosis in H460 lung cancer cells significantly. 22 Similarly, we also observed that resveratrol suppressed cell proliferation and induced apoptosis in NSCLC cells, indicating the anti-tumor effect of resveratrol in NSCLC progression.…”
Section: Discussionmentioning
confidence: 98%
“… 20 Research by Kim et al showed that res-veratrol induced mitochondrial apoptosis and inhibited cell invasion and migration by inhibiting epithelial–mesenchymal transition in oral squamous cell carcinoma cells. 21 Resvera-trol was also reported to decrease cell viability and proliferation while induced apoptosis in H460 lung cancer cells significantly. 22 Similarly, we also observed that resveratrol suppressed cell proliferation and induced apoptosis in NSCLC cells, indicating the anti-tumor effect of resveratrol in NSCLC progression.…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Lei et al (25), RV decreased proliferation, enhanced cellular differentiation and improved melanin generation in HT-144 melanoma cells through inhibiting the mitogen-activated protein kinase kinase/ERK kinase pathway. Kim et al (26) revealed that RV triggered cell death in the mitochondrial pathway. Furthermore, RV reduced survival and enhanced apoptosis in H460 lung cancer cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…In oral squamous cell carcinoma cells, resveratrol can suppress cell invasion and migration by decreasing the expression of EMT-inducing transcription factors. 228 During cancer chemotherapy, acquired Doxorubicin resistance severely impedes the therapeutic effect, invariably leading to poor prognosis. In gastric cancer, resveratrol can reverse Doxorubicin resistance by interfering with the EMT process via modulation of PTEN/Akt signaling.…”
Section: Tcm For Prevention Of Emt and Metastasismentioning
confidence: 99%